Analysis of 5′-NAD capping of mRNAs in dormant spores of Bacillus subtilis. Issue 17 (21st August 2020) - Craft, D Levi; Korza, George; Zhang, Yaqing; Frindert, Jens; Jäschke, Andres; Caimano, Melissa J; Setlow, Peter
ABSTRACT: Spores of Gram-positive bacteria contain 10s–1000s of different mRNAs. However, Bacillus subtilis spores contain only ∼ 50 mRNAs at > 1 molecule/spore, almost all transcribed only in the developing spore and encoding spore proteins. However, some spore mRNAs could be stabilized to ensure they are intact in dormant spores, perhaps to direct synthesis of proteins essential for spores' conversion to a growing cell in germinated spore outgrowth. Recent work shows that some growing B. subtilis cell mRNAs contain a 5′-NAD cap. Since this cap may stabilize mRNA in vivo, its presence on spore mRNAs would suggest that maintaining some intact spore mRNAs is important, perhaps because they have a translational role in outgrowth. However, significant levels of only a few abundant spore mRNAs had a 5′-NAD cap, and these were not the most stable spore mRNAs and had likely been fragmented. Even higher levels of 5′-NAD-capping were found on a few low abundance spore mRNAs, but these mRNAs were present in only small percentages of spores, and had again been fragmented. The new data are thus consistent with spore mRNAs serving only as a reservoir of ribonucleotides in outgrowth. Abstract : Few Bacillus subtilis spore mRNAs had 5'-NAD, but these were neither stable nor intact, consistent with them being a ribonucleotide reserve used in outgrowth, as likely are all spore mRNAs.